PENERAPAN TEKNOLOGI MESIN PENGADUK MEDIA TANAM JAMUR TIRAM PUTIH DI SENTRA JAMUR PONDOK PESANTREN DARUSSALAM LAMPUNG SELATAN - Irza Sukmana (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2017)
Abstrak Pleurotus ostreatus mushroom cultivation is a promising business opportunities in Bandar Lampung, as for one mushroom’s growing media (baglog) may produces for harvesting mushrooms every day up to 4-5 months. However, the success and quality of the mushroom production depends on the quality of mushroom’s growing media (baglog) preparation. Baglog preparation process is done through several steps, starting with preparing and mixing the raw materials to get a homogeneous and optimal dough, then subsequent compression and packaging of growing media in a plastic bag, before sterilizing and placing the oyster mushrooms stem at the top of baglog. In the small-scale mushroom industry, the process of mixing and compression of growing media used to be done manually or by human power. This process may give a low degree of homogeneity and uncompact baglog. The objection of this community service program is to implement an automatic mixer and compression tools for baglog production at oyster mushroom plantation center at Pesantren Darussalam, Banjar Negeri, Natar, South Lampung. Kata kunci: Pleurotus ostreatus mushroom, baglog, mixer machine, compression tool